Técnicas de prospección geoquímica para uranio en colombia (1975)
The method described herein was developed by the Commissariat à I'Énergie Atomique (CEA) of France (1958), completed by The Comitato Nazionale per l'Energia Nucleare (CNEN), and applied in the Instituto of Nuclear Affairs of Colombia, the technique is based on a cuantitative determination of Uranium traces present in water, rocks and alluvial deposits. The sensitivity of determination is 0,1 ppb in water and 0,1 ppm in alluvial deposits and rocks. The method is efficient, economic and permits to cover large areas in short time, obtaining a fast individualization of geochemistry anomalous, specially in mountainons and difficult access areas. An orientation prospection was carried out in the area of California, Santander; where it had been determined high radiometric counts and Uranium minerals. The results were successfull and showed the effectiveness of the method.